Influence of Rho/ROCK inhibitor Y-27632 on proliferation of equine mesenchymal stromal cells - Melzer, Michaela; Burk, Janina; Guest, Deborah J.; Dudhia, Jayesh (Frontiers in Veterinary Science, 2023)
Mesenchymal stromal cells (MSC) isolated form bone marrow and adipose tissue are the most common cells used for cell therapy of orthopedic diseases. MSC derived from different tissues show differences in terms of their proliferation, differentiation potential and viability in prolonged cell culture. This suggests that there may be subtle differences in intracellular signaling pathways that modulate these cellular characteristics. The Rho/ROCK signaling pathway is essential for many cellular functions. Targeting of this pathway by the ROCK inhibitor Y-27632 has been shown to be beneficial for cell viability and proliferation of different cell types. The aim of this study was to investigate the effects of Rho/ROCK inhibition on equine MSC proliferation using bone marrow-derived MSC (BMSC) and adipose-derived MSC (ASC). Primary ASC and BMSC were stimulated with or without 10 ng/mL TGF-β3 or 10 μM Y-27632, as well as both in combination. Etoposide at 10 μM was used as a positive control for inhibition of cell proliferation. After 48 h of stimulation, cell morphology, proliferation activity and gene expression of cell senescence markers p53 and p21 were assessed. ASC showed a trend for higher basal proliferation than BMSC, which was sustained following stimulation with TGF-β3. This included a higher proliferation with TGF-β3 stimulation compared to Y-27632 stimulation (p < 0.01), but not significantly different to the no treatment control when used in combination. Expression of p21 and p53 was not altered by stimulation with TGF-β3 and/or Y-27632 in either cell type. In summary, the Rho/ROCK inhibitor Y-27632 had no effect on proliferation activity and did not induce cell senescence in equine ASC and BMSC.